2015
DOI: 10.1002/2015wr017261
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dynamic factors on nonwetting fluid snap‐off in pores

Abstract: Snap-off is an important dynamic multiphase flow phenomenon which occurs in porous media.It plays a dominant role in the residual trapping and mobilization/immobilization of nonwetting fluids such as hydrocarbons or CO 2 . Current studies, applications, and threshold criteria of snap-off are mostly based on static or equilibrium conditions. Thus, the dynamics of snap-off which is relevant for many real world applications has rarely been systematically studied. While a static criterion indicates the snap-off po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…Numerous studies have shown that dimensionless parameters, such as the capillary number and viscosity ratio, can influence displacement flow patterns and thus capillary pressure and relative permeability functions (Aggelopoulos & Tsakiroglou, ). A sufficiently large local CA can inhibit snap‐off (an important dynamic multiphase flow phenomenon) of multiple fluids (Deng et al, ). The motion of a drop through a constriction is therefore relatively steady, but the flow is clearly unsteady in the pore networks of a medium (Olbricht, ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that dimensionless parameters, such as the capillary number and viscosity ratio, can influence displacement flow patterns and thus capillary pressure and relative permeability functions (Aggelopoulos & Tsakiroglou, ). A sufficiently large local CA can inhibit snap‐off (an important dynamic multiphase flow phenomenon) of multiple fluids (Deng et al, ). The motion of a drop through a constriction is therefore relatively steady, but the flow is clearly unsteady in the pore networks of a medium (Olbricht, ).…”
Section: Introductionmentioning
confidence: 99%
“…A uniform thickness of the wetting film δ * was considered throughout the capillary wall as an initial condition (see Fig. 1); which was calculated using the fitting made by Deng et al (2015) of Beresnev et al (2011b) experimental data. This fitting was established as a function of the local capillary number as δ * =0.0412log10(Ca)+0.1475, and is valid in the range of 3×10 -4 ≤ Ca ≤ 1×10 -2 .…”
Section: Governing Equationsmentioning
confidence: 99%
“…This fitting was established as a function of the local capillary number as δ * =0.0412log10(Ca)+0.1475, and is valid in the range of 3×10 -4 ≤ Ca ≤ 1×10 -2 . In the simulations presented here, we explored the same ranges of dimensionless geometric variables that Deng et al (2015) did, namely: 2 ≤ L ≤16 and 0.20 ≤ a ≤ 0.50. The maximum dimensionless simulation time was also established in τmax= 2×10 5 .…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate estimation of trapped, nonmobile, nonwetting phase fluid in the subsurface is a critical parameter for engineering processes such as enhanced oil recovery, geologic CO 2 sequestration, and contaminant remediation. To this end, many previous studies have attempted to link trapping levels to porous media structural characteristics (e.g., Chatzis & Morrow, 1984;Li & Wardlaw, 1986b;Wardlaw & Li, 1988), in addition to fluid-fluid interactions (e.g., Bennion & Bachu, 2013;Kimbrel et al, 2015;Morrow et al, 1988) and dynamic influences (Deng et al, 2015;Singh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%